2013
DOI: 10.1523/jneurosci.0114-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Expectation and Attention in Hierarchical Auditory Prediction

Abstract: Hierarchical predictive coding suggests that attention in humans emerges from increased precision in probabilistic inference, whereas expectation biases attention in favor of contextually anticipated stimuli. We test these notions within auditory perception by independently manipulating top-down expectation and attentional precision alongside bottom-up stimulus predictability. Our findings support an integrative interpretation of commonly observed electrophysiological signatures of neurodynamics, namely mismat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
286
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(343 citation statements)
references
References 59 publications
34
286
2
2
Order By: Relevance
“…While we found the auditory N1 to be enhanced under attended conditions, consistent with previous reports on early effects of attention on brain responses (Picton and Näätänen, 1987;Chennu et al, 2013), the effects of attention (i.e., an enhancement) and prediction (i.e., a suppression followed by a rebound) were clearly independent of each other. The independency of the two effects is in line with the findings that repeated sounds are associated with suppressed auditory N1 regardless of attention allocation (Haenschel et al, 2005;Hsu et al, 2014a).…”
Section: Discussionsupporting
confidence: 92%
“…While we found the auditory N1 to be enhanced under attended conditions, consistent with previous reports on early effects of attention on brain responses (Picton and Näätänen, 1987;Chennu et al, 2013), the effects of attention (i.e., an enhancement) and prediction (i.e., a suppression followed by a rebound) were clearly independent of each other. The independency of the two effects is in line with the findings that repeated sounds are associated with suppressed auditory N1 regardless of attention allocation (Haenschel et al, 2005;Hsu et al, 2014a).…”
Section: Discussionsupporting
confidence: 92%
“…2). This effect has been previously associated with an expectation of the fifth sound in the sequence (40), an interpretation that would appear to contradict the observed disruption of predictions during sleep. However, this ramping-up also can be interpreted as a passive summation of the activation evoked by each successive vowel, without involving top-down expectations.…”
Section: Discussionmentioning
confidence: 77%
“…2). In the local-global paradigm with awake and conscious subjects, a progressive ramping-up of brain responses across the four sounds has been described and tentatively ascribed to an expectation of the final sound (40). We verified that this ramping-up was present in our data during wakefulness (cluster analysis for slope different from 0, P < 0.001 in temporal areas), and that it diminished during N1 sleep and then N2 sleep (Table S7) while remaining significant (significant slope in N2 sleep, P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…First described by Grey Walter et al in 1964 [41], CNV is a sustained negativity that can be observed in between 250-450 ms after the warning stimulus, during the interval in between the warning stimulus and the imperative. CNV is mainly considered to reflect response preparation and it varies with stimulus features, such as intensity, probability, relevance, pitch, and duration (e.g., [42]) as well as attentional engagement [43].…”
Section: Contingent Negative Variation Contingent Negativementioning
confidence: 99%